The Impact of the Basel III Framework Implementation on Banking Performance in Indonesia - Andri Tri Wibowo; Noer Azam Achsani; Zenal Asikin (Institut Bisnis dan Informatika Kesatuan, 2026)
Banking stability is crucial to Indonesia’s financial resilience. Following the 2008 global crisis, Basel III was introduced to reinforce banks’ capital, leverage, and liquidity frameworks. This study aims to analyze the impact of the implementation of the Basel III framework on the financial performance of Indonesian banks, particularly on profitability and operational efficiency during the 2018-2024 period. This study uses secondary quantitative data obtained from the annual financial statements and published reports of publicly listed conventional commercial banks. The collected data include information related to Basel III implementation. Data processing methods used descriptive analysis and dynamic common correlated effects panel data regression analysis. The research data are sourced from financial reports officially published by each bank. The results show that the success of Basel III implementation depends not only on compliance levels but also on each bank’s ability to balance stability, efficiency, and growth. For banks, capital optimization, leverage management, and adaptive liquidity strategies are key. Regulators require proportional policy calibration and risk-based supervision. With the right approach, Basel III can be a strategic instrument for sustainably strengthening the competitiveness and resilience of the national banking system.